Competitive Adsorption among Phospholipids at Oil Globule Interface of Caseinate Stabilized Emulsion - Estiasih, Teti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
Casein and phospholipids are natural compounds usually used concomitantly as emulsifier. This research was conducted to elucidate the adsorbed phospholipids composition that stabilized oil globule interface during fish oil emulsification by sodium caseinate and phospholipids. Emulsion was formed by homogenizing sodium caseinate solution (10% w/v) with various phospholipids concentration of 0, 0.5, 1.0, 1.5, 2.0, and 2.5% (w/v) at fish oil concentration of 20%. The results showed that the quantity of adsorbed phospholipids increased in line with increasing phospholipids concentration. Competitive adsorption occured among various phospholipids that indicated by compositional changes of adsorbed phospholipids at oil globule interface. Their preference to adsorb was influenced by their surface activities. Among various phospholipids, phosphatidylcholine had preference to adsorb due to its higher surface activity and quantity. Phosphatidylethanolamine had less preference to adsorb because of its lower surface activity. Meanwhile, phosphatidylinositol had less ability to compete due to its low quantity. The change of adsorbed layer in oil globule interface was caused by phospholipids-casein complexation and displacement of casein by phospholipids to occupy oil globule interface. Keywords: preference to adsorb, caseinate, phospholipids, emulsion, oil globule, interface, surface activity, competitive adsorption, displacement, adsorbed layer, complexation